Persepsi Mahasiwa Magang terhadap Sistem Pelayanan Pajak di KPP Pratama Mojokerto - Rafaelani Putri Kristanti; Amrina Yulfajar (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
This study aims to examine how student interns perceive the performance of tax services at the Mojokerto Tax Office (KPP). This study employs a qualitative approach using descriptive methods. Data were collected through interviews with interns assigned to the service division, specifically at the Integrated Service Center (TPT). The interview results indicate that the tax service framework at the Mojokerto Primary Tax Office is viewed positively, is well-organized, and is beginning to evolve toward a modern and digital service approach through CORETAX technology. The shift toward digital services is believed to improve efficiency, streamline the process of obtaining a Taxpayer Identification Number (NPWP), simplify annual tax reporting, and enhance access to additional tax services. Additionally, the quality of service provided by staff was rated as friendly, professional, interactive, and supportive in helping taxpayers understand the service process. Nevertheless, several challenges were noted, including a lack of general awareness among taxpayers regarding digital platforms particularly among older taxpayers increased wait times during the annual tax filing season, and occasional system disruptions that affected service delivery. Based on interview findings, the tax service framework at the Mojokerto Pratama Tax Office is considered fairly efficient, although there is still room for improvement in promoting the adoption of digital services, enhancing service facilities, and creating a more user-friendly system.